Developing early maturing and stress-tolerant potato varieties for Asia. Project profile. - International Potato Center (International Potato Center, 2019)
Climate change is increasingly threatening food security throughout the developing world, and there is urgent need for new, stress-tolerant varieties of major crops like potato. This project focuses on breeding early-maturing, stresstolerant potato varieties to boost productivity and incomes for farmers across Central and East Asia.